Effect of climate dataset selection on simulations of terrestrial GPP - Wu, Zhendong; Lehsten, Veiko (Lund University, 2018)
This dataset contains the GPP output (1979-2010) from LPJ-GUESS using six historical climate datasets (CRU, CRUNCEP, ECMWF, NCEP, PRINCETON, and WFDEI), the results of the analysis from Wu et al. (2018): Effect of climate dataset selection on simulations of terrestrial GPP: highest uncertainty for tropical regions.
Keywords: Environmental Sciences; Miljövetenskap